2017
DOI: 10.1002/pssa.201700304
|View full text |Cite
|
Sign up to set email alerts
|

Recombination via transition metals in solar silicon: The significance of hydrogen–metal reactions and lattice sites of metal atoms

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.The move toward lower cost sources of solar silicon has intensified the efforts to investigate the possibilities of passivating or reducing the recombination activity caused by deep states associated with transition metals. This is particularly important for the case of the slow diffusing metals early in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…This explains our previous observation that changing the cooling rate has a negligible influence on the measured lifetimes, as shown in Figure . However, our result disagrees with some previous works that suggest that the passivation reaction mainly occurs during the cooling down period because the binding between hydrogen and metals are rather weak and unstable at high temperature (higher than 200°C) . Moreover, it is found that the same inactive hydrogenated GB became recombination active and remained active afterwards when subjected to a second annealing without the presence of hydrogen containing dielectric films on the surfaces, possibly due to the out diffusion of hydrogen from the Si bulk to the ambient.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This explains our previous observation that changing the cooling rate has a negligible influence on the measured lifetimes, as shown in Figure . However, our result disagrees with some previous works that suggest that the passivation reaction mainly occurs during the cooling down period because the binding between hydrogen and metals are rather weak and unstable at high temperature (higher than 200°C) . Moreover, it is found that the same inactive hydrogenated GB became recombination active and remained active afterwards when subjected to a second annealing without the presence of hydrogen containing dielectric films on the surfaces, possibly due to the out diffusion of hydrogen from the Si bulk to the ambient.…”
Section: Resultscontrasting
confidence: 99%
“…The underlying mechanism of bulk hydrogenation in mc‐Si is less clear. There is still a lack of consensus in literature on how hydrogen diffuses from the dielectric films into Si bulk, exactly which defects can be passivated, and the fundamental physics of the passivation reaction . In previous work, we found that hydrogenation is effective in passivating GBs but rather ineffective for passivation of dislocation clusters and hence is particularly beneficial for high‐performance (HP) mc‐Si that contains a large density of GBs and a lower density of dislocation clusters …”
Section: Introductionmentioning
confidence: 99%
“…. Secondly, although not directly proven to our knowledge at these temperatures, various authors have provided evidence to suggest that hydrogen diffuses into the bulk from the dielectric layers, and hydrogen has the potential to affect bulk lifetime by interacting with other defects . Thirdly, impurities such as iron have been shown to be highly soluble in dielectrics such as SiN x and can be gettered to the Al 2 O 3 –Si interface and thus sufficiently mobile metallic impurities can be potentially removed from the bulk during the passivation step.…”
Section: Motivation For Temporary Passivationmentioning
confidence: 96%
“…Hydrogenation of Silicon wafers has been recurrently applied in order to passivate, or at least reduce, the recombination activity from several defects and contaminants, including iron and other transition metals. 2,[5][6][7][8][9][10] In Si photovoltaics this hydrogenation process is usually accomplished by means of depositing and firing a hydrogensoaked SiN x layer on top of Si, which besides the surfacepassivation effect, it also works as an anti-reflection coating for the front surface of the cell. 11,12 Other types of hydrogen introduction for passivation treatments have also been considered, including proton implantation 13 or H-plasma exposure, 14 but none is as convenient as the nitridation process.…”
Section: Introductionmentioning
confidence: 99%